Multi-layered composite detectors for neutron detection - Ryzhikov, V.D.; Grinyov, B.V.; Boyarintsev, A.Yu.; Tinkova, V.S.; Maksymchuk, V.V.; Yakubovskaya, A.G.; Tupitsyna, I.A. (Functional Materials, 2018)
The paper considers the influence of manufacturing technological features of composite scintillator with optimal scintillation characteristics based on heavy-oxide crushed single crystals for making ZEBRA-detectors for fast neutrons registration. It has been shown that registration efficiency of fast neutrons by multi-layered ZEBRA-detectors based on crushed Bi₄Ge₃O₁₂, Gd₂SiO₅:Ce and ZnWO₄ crystals achieved the value about 50 %. Sensitivity of ZEBRA-detectors with size of 100×100×41 mm³ is comparable to sensitivity of 3He counter with moderator. ZnWO4 powder obtained by solid state synthesis is proposed as an alternative filler to crushed crystal powders for scintillation composite. Results of measurements of technical detection efficiency and sensitivity for fast neutrons (sources Pu-Be and ²⁵²Cf) showed that detection efficiency of ZEBRA-detector based on synthesized scintillation ZnWO₄ powder is comparable with detector based on crushed ZnWO₄ single crystal of the same size. Qualitative explanations are presented for abnormal high sensitivity of multi-layered composite detectors. ZEBRA-detector is promising for application in the field of homeland security and nuclear safeguards.